2018
DOI: 10.1186/s12889-018-5112-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the rapid increase in life expectancy in shanghai, China: a population-based retrospective analysis

Abstract: BackgroundLife expectancy at birth (LE) is a comprehensive measure that accounts for age-specific death rates in a population. Shanghai has ranked first in LE in China mainland for decades. Understanding the reasons behind its sustained gain in LE provides a good reflection of many other cities in China. The aim of this study is intended to explore temporal trend in age- and cause-specific gains in LE in Shanghai and the probable reasons lay behind.MethodsJoinpoint regression was applied to evaluate temporal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…From 1990 to 2002, CMNNs played an important role in the contributions to LE which were mainly influenced by infant mortality rate. Reductions of infant mortality in diarrhea, lower respiratory, and other common infectious diseases and neonatal disorders contributed most to LE, which was consistent with results in other studies [23,24]. Steady declines in fertility, comprehensive universal health insurance and the effective promotion of national health policy for children pediatric healthcare, including implementations of one-child family planning, immunization and nutritional support may account for the contributions from infant mortality [25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…From 1990 to 2002, CMNNs played an important role in the contributions to LE which were mainly influenced by infant mortality rate. Reductions of infant mortality in diarrhea, lower respiratory, and other common infectious diseases and neonatal disorders contributed most to LE, which was consistent with results in other studies [23,24]. Steady declines in fertility, comprehensive universal health insurance and the effective promotion of national health policy for children pediatric healthcare, including implementations of one-child family planning, immunization and nutritional support may account for the contributions from infant mortality [25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…Among all its provinces, Shanghai has ranked first in LE in China mainland for many years 11 , with low mortality even by the standards of high-income countries. Our previous study showed that after a period of decline and recovery, LE in Shanghai finally increased from 71 years in the 1970s to 84 years in 2018, and is still on the rise 12 .…”
Section: Introductionmentioning
confidence: 97%
“…Impaired renal function, often deteriorating continuously and resulting to end-stage renal disease, is the common chronic complication in diabetes. Diabetic kidney disease (DKD) has become the main cause in patients requiring renal replacement therapy [1,2]. It's important to look for controllable risk factors to take appropriate measures to inhibit diabetic renal function to worse.…”
Section: Introductionmentioning
confidence: 99%